Genome-wide identification and expression analysis of WRKY family genes under soft rot in Chinese cabbage - Yan, Jinghui; Yu, Xinle; Ma, Wei; Sun, Xiaoxue; Ge, Yunjia; Yue, Xiaonan; Han, Jing; Zhao, Jianjun; Lu, Yin; Liu, Mengyang (Frontiers in Genetics, 2022)
Complex transcriptional networks regulate plant defense against pathogen attack, and plant transcription factors act as key regulators of the plant immune responses. The differences in transcription factor expression and regulation between Chinese cabbage soft rot (Pectobacterium carotovorum; Pc) have not been revealed. In this study, a total of 148 putative Chinese cabbage WRKY genes (BrWRKYs) were identified from Chinese cabbage genome (v3.0). These genes were divided into seven subgroups (groups I, IIa-e, and III) based on phylogenomic analysis, with distinct motif compositions in each subgroup. Time-series RNA-seq was carried out to elucidate the dynamic expression patterns of the BrWRKYs on the resistant mutant (sr) and the susceptible wild type (inbred WT) challenged by Pc. Transcriptional analysis showed that 48 WRKY transcription genes at 0-24 hpi were significantly upregulated in sr under soft rot stress. At the 12 hours post inoculation critical time point, we identified three specifically upregulated genes and two downregulated genes in the resistant mutant, which may provide potential applications for genetic improvement against soft rot. The findings improved our understanding of the WRKY-mediated soft rot stress response regulation in Chinese cabbage. The study thus lays a foundation for the genetic improvement of soft rot resistance.